2015
DOI: 10.1149/2.0051512ssl
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Constancy of Passivation-Free Ultra-Thin Zinc Tin Oxide Thin Film Transistor

Abstract: An ultra-thin (5 nm-thick), unpassivated zinc tin oxide (ZTO) thin-film transistor TFT, fabricated with solution process, exhibits a good field-effect mobility (13 ∼ 14 cm 2 /Vs), small subthreshold swing (∼0.30 V/dec.) and high on/off current ratio (∼10 8 ). The field-effect mobility can be further enhanced by increasing the ZTO thickness to 12 nm and 22 nm. Furthermore, I D -V G characteristics of the 5 nm-thick ZTO TFT remain unaffected, regardless of working in air (60% relative humidity), vacuum or dry O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[59] In addition to improving the switching and turn-on properties of the devices, optimizing substrate preparation and the insulator deposition process may improve field-effect mobility to more closely rival quaternary indium-containing ALD TFTs. [60] Prior work, using different deposition techniques or semiconductor oxides, has shown that activelayer thickness must be optimized to obtain good TFT stability [61] and enhancement mode behavior. [62] To investigate the effect of ZTO layer thickness on TFT behavior, three identical devices were fabricated using 5, 9, and 13 nm ZTO films deposited using the thermal ALD process at 200 ºC with post-deposition annealing at 500 ºC.…”
Section: Electrical Properties Of Ald Zto Thin-film Transistorsmentioning
confidence: 99%
“…[59] In addition to improving the switching and turn-on properties of the devices, optimizing substrate preparation and the insulator deposition process may improve field-effect mobility to more closely rival quaternary indium-containing ALD TFTs. [60] Prior work, using different deposition techniques or semiconductor oxides, has shown that activelayer thickness must be optimized to obtain good TFT stability [61] and enhancement mode behavior. [62] To investigate the effect of ZTO layer thickness on TFT behavior, three identical devices were fabricated using 5, 9, and 13 nm ZTO films deposited using the thermal ALD process at 200 ºC with post-deposition annealing at 500 ºC.…”
Section: Electrical Properties Of Ald Zto Thin-film Transistorsmentioning
confidence: 99%
“…With each additional periodic layer to the QSL, the top surface remains essentially identical, as a clean well-defined interface. A higher O vacancy content promotes n-type character as donors but also provides exceptional ambient air (moisture, O-containing air) stability for channel materials, as discussed by Liu et al 53 The surface electronic structure from Zn 2p and O 1s core-level photoemission is consistent and independent of QSL thickness. There is, however, a very slight shift in the binding energy of the Zn 2p spectra for a 1 L film.…”
Section: Zno Qsl Surface Composition and Electronic Structurementioning
confidence: 80%
“…Consequently, the V on negatively shifts with increasing t ITO and the µ FE increases with t ITO increasing from 6 to 9 nm. However, similar to other impurity dopants, more oxygen defects can induce more ionized impurity scattering, which possibly results in the degradation of µ FE with t ITO increasing from 9 to 15 nm [24]. 529.7 eV and O2 peak at around 531.3 eV, which can be regarded as metal-oxygen lattice and oxygen defects (oxygen vacancies and chemisorbed oxygen element), respectively [21].…”
Section: Electrical Characteristics Of Ito Tftsmentioning
confidence: 99%
“…Consequently, the Von negatively shifts with increasing tITO and the µFE increases with tITO increasing from 6 to 9 nm. However, similar to other impurity dopants, more oxygen defects can induce more ionized impurity scattering, which possibly results in the degradation of µFE with tITO increasing from 9 to 15 nm [24]. Drain current-drain voltage (ID-VD) curves of the ITO TFTs are measured, as shown in Figure 7a-d.…”
Section: Electrical Characteristics Of Ito Tftsmentioning
confidence: 99%